2006
DOI: 10.1093/jnci/djj161
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic Cell Death of Malignant Glioma Cells Induced by a Conditionally Replicating Adenovirus

Abstract: hTERT-Ad may kill telomerase-positive cancer cells by inducing autophagic cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
151
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(160 citation statements)
references
References 53 publications
7
151
1
1
Order By: Relevance
“…In contrast, in a more recent publication, an hTERT-Ad vector was shown to induce autophagic cell death in tumor cells (22). In this study, our aim was to explore the role of the survivin promoter in CRAd mediated oncolysis of human glioma.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In contrast, in a more recent publication, an hTERT-Ad vector was shown to induce autophagic cell death in tumor cells (22). In this study, our aim was to explore the role of the survivin promoter in CRAd mediated oncolysis of human glioma.…”
Section: Introductionmentioning
confidence: 91%
“…Autophagy was assessed in No. 10 cells by the quantification of acidic vesicular organelles with supravital cell staining using acridine orange, as described previously (22,25). Cells were grown in square coverslips 24 h before infection.…”
Section: Cell Cycle Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are only two reports showing that virus-induced ecto-CRT was correlated with enhanced intratumoral infiltrations of immune subpopulations, which accounted for the 'in vivo' remarkable antitumor immunity. 9,65 Several studies showed that recombinant oncolytic adenoviruses induced ACD in human malignant glioma cells, 120 brain tumor stem cells, 121 osteosarcoma cells, 105 and lung cancer cells. 122 Newcastle disease virus also triggered autophagy in glioma cells to promote its viral replication.…”
Section: Different Types Of Immunogenic Cancer Cell Death H Inoue Andmentioning
confidence: 99%
“…It is known that infection results in a rounded shape and condensation of the cytoplasm, that is, cytopathic effect (CPE). Apoptotic and necrotic mechanisms have been proposed and recent studies 14,15 suggest that Ad infected cancer cells feature autophagy, a form of programmed cell death distinct from apoptosis, characterized by the degradation of intracellular components via the lysosome. 16 Radiation alone has also been shown to induce autophagy.…”
Section: Uiccmentioning
confidence: 99%